2006
DOI: 10.1007/s00276-006-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Arteriography of three models of gastric oesophagoplasty: the whole stomach, a wide gastric tube and a narrow gastric tube

Abstract: The esogastric anastomotic fistula,occurring after the replacement of esophagus by the stomach, is a post-operative complication always feared and awaited. Apart from other causes, there exist the anatomical dispositions notably the vascular and technical factors that stress this potential risk despite certain advantages of esophagogastroplasty. The goal of our study was to study the arterial distribution of the gastric transplants in order to identify the better modalities of their making. We used 39 stomachs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 11 publications
1
14
0
2
Order By: Relevance
“…A knowledge of anatomy points to the variability of the gastroepiploic arcade as a possible cause. The work of Koskas and Gayet [39], Yamato et al [40], and more recently, Ndoye et al [41] warned against an inconstant vascular supply of the stomach, a fact that can be easily missed due to the loss of tactile and proprioceptive feedback during an MIO. Some authors have suggested modifying the procedure to include a minilaparotomy to deliver the stomach and fashion the conduit outside the body, promoting surgical sensory feedback, with a possible lower failure rate [8,25].…”
Section: Discussionmentioning
confidence: 98%
“…A knowledge of anatomy points to the variability of the gastroepiploic arcade as a possible cause. The work of Koskas and Gayet [39], Yamato et al [40], and more recently, Ndoye et al [41] warned against an inconstant vascular supply of the stomach, a fact that can be easily missed due to the loss of tactile and proprioceptive feedback during an MIO. Some authors have suggested modifying the procedure to include a minilaparotomy to deliver the stomach and fashion the conduit outside the body, promoting surgical sensory feedback, with a possible lower failure rate [8,25].…”
Section: Discussionmentioning
confidence: 98%
“…Atherosclerosis, a known cause of ischemia, has been reported to compromise the blood supply of the gastric tube and cervical anastomosis (9). It has also been reported that calcification of the aortic wall and supra-aortic arteries can be used to predict cardiovascular events (10).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the reliability of this study, another radiologist (J-J), who was also blinded to the data of patients, was also invited to evaluate CT imaging. The selection of investigated vessels was based on anatomic studies, which showed that the right gastroepiploic artery exclusively supplies the gastric tube and originates from the aorta via the celiac axis, common hepatic artery, and gastroduodenal artery (9,15). Furthermore, calcifications in the splenic and left gastroepiploic arteries were assessed because it has been reported that about 20% of the gastric tube is supplied by the left gastroepiploic arteries before divided (15).…”
Section: Imaging Acquisition and Assessmentmentioning
confidence: 99%
“…This also explains the increased occurrence of leak following cervical esophagogastric anastomosis, where the length of the gastric tube is necessarily extended and the gastric tip becomes more remote from its collateral blood supply [21].…”
Section: Discussionmentioning
confidence: 98%